Тестовая оценка точности решения задачи компараторной идентификации параметров модели многофакторного оценивания - Петров, К. Э. (ХНУРЭ, 2008)
This work is devoted the analysis of results of test modeling with the purpose of estimation of exactness, adequacy and calculable complication of decision of problem of parametrical identification of the model of multifactor estimation. Exactness of identification substantially depends on the concrete features of problem, such as a quantity of local descriptions of alternatives, power of the set of alternatives, complication of polynomial and method of identification. As a class of possible structures of the model of estimation is suggested to use the polynomial of Kolmogorov-Gabor